(untitled) (Research, Society and Development, 2023)
Severe caries in early childhood can cause coronary destruction and negatively affect children’s quality of life. It compromises aesthetics, phonation and promotes weight loss, growth deficit, changes in sleep patterns and behavioral patterns, social exclusion and low self-esteem. The cessation of caries disease with changes in hygiene and diet habits precedes the reconstruction of dental elements. Methodology: this work is a qualitative and descriptive study, of the case report type, elaborated through anamnesis, dental history, as well as photographs of the patient. Objective: This work consists of demonstrating a clinical case of aesthetic rehabilitation in anterior deciduous teeth affected by severe caries in childhood, in female patient aged 3 years and 0 months. As an option for rehabilitation, it was decided to use a zirconia crown and acetate matrices with composite resin, restoring the lost aesthetics and self-esteem of the child patient. Final considerations: Acetate crowns and zirconia crowns are excellent options for aesthetic rehabilitation in primary dentition.